A Rare Case Report on Benign Recurrent Intrahepatic Cholestasis (Faridpur Medical College Journal, 2015)
Benign recurrent intrahepatic cholestasis is an inherited and occasionally sporadic disease presents as recurrent episodes of obstructive jaundice without any obstruction in billiary channel with intervening symptom free periods. Here we are presenting a case of 20-year-old male with a recurrent jaundice and pruritus who later diagnose as BRIC.Faridpur Med. Coll. J. 2014;9(2): 108-110